The role of rotational mechanisms in electron swarm parameters at low reduced electric field in N2, O2 and H2. (29th April 2015) - Ridenti, M A; Alves, L L; Guerra, V; Amorim, J
Abstract: The homogeneous Boltzmann equation for electrons in N2, O2 and H2 is solved under the classical two-term approximation, for reduced electric fields in the interval 10   −  4   −10 Td where the electron-neutral encounters are limited to elastic, rotational and vibrational collisions. Rotational excitations/de-excitations are described using the following three different approaches: the discrete inelastic/superelastic collisional operator, written for a number of rotational levels that depends on the molecular gas and the specific rotational cross sections considered; the continuous approximation for rotations; a modified version of the continuous approximation for rotations, including a Chapman–Cowling corrective term proportional to the gas temperature. The expression of the rotational collision operator for this latter approach is deduced here and the results show that it bridges the gap between the discrete and the continuous descriptions at low/intermediate reduced electric fields. The calculations are compared with the measurements for the available swarm parameters to assess the validity of the different approaches and cross sections adopted to describe the rotational mechanisms.